AUTOMATED SYSTEM OF THE OPERATIONAL ANALYSIS OF THE FEASIBILITY OF EARTH REMOTE SENSING - N. A. Arkhipova; S. A. Zolotoy; V. M. Korzun; V. D. Kastsiuchenka; V. E. Kupryianets; A. A. Sobal (Системный анализ и прикладная информатика, 2016)
The article scopes the hardware and software of the information system for pre-contractual real-time analysis of requests feasibility for supplying of Earth remote sensing data, which is an integral part of the Belarusian Space System for Earth Remote Sensing. The main purpose of the development of this information system is the creation of computer-aided system for real-time analysis of customers’ requests feasibility by using the resources of two space vehicles. This system is a decision support system in the pre-contractual phase on the everyday business practice. This automation activity is solved using multicriteria optimization approaches. The created information system allows to speed-up calculations and increase its quality as well as to augment the precision of assessment of space images acquisition by including the resources of two satellites during the requested period of time. This system has passed the evaluation test for both satellites and may be further used as the base for real-time analysis of requests feasibility taking into account the resources of several space vehicles.